2006
DOI: 10.1016/j.ccr.2006.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression-based chemical genomics identifies rapamycin as a modulator of MCL1 and glucocorticoid resistance

Abstract: Drug resistance remains a major obstacle to successful cancer treatment. A database of drug-associated gene expression profiles was screened for molecules whose profile overlapped with a gene expression signature of glucocorticoid (GC) sensitivity/resistance in acute lymphoblastic leukemia (ALL) cells. The screen indicated that the mTOR inhibitor rapamycin profile matched the signature of GC sensitivity. We tested the hypothesis that rapamycin would induce GC sensitivity in lymphoid malignancy cells and found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
435
2
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 484 publications
(465 citation statements)
references
References 61 publications
23
435
2
5
Order By: Relevance
“…In contrast to MLLrearranged infant ALL, high-level S100A8/S100A9 expression appeared largely absent in other types of childhood ALL (Figure 1b), suggesting that the inhibition of MCL1 in prednisolone resistant non-infant pediatric precursor B-ALL cells may be far more effective. 9,10 Furthermore, we show that high-level expression of S100A8 and S100A9 is not only associated with in vitro prednisolone resistance, but also correlates (although not significantly) with poor in vivo prednisone responses. Interestingly, the level of S100A8/A9 expression appeared a stronger predictor of a poor clinical outcome than the in vivo prednisone response.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In contrast to MLLrearranged infant ALL, high-level S100A8/S100A9 expression appeared largely absent in other types of childhood ALL (Figure 1b), suggesting that the inhibition of MCL1 in prednisolone resistant non-infant pediatric precursor B-ALL cells may be far more effective. 9,10 Furthermore, we show that high-level expression of S100A8 and S100A9 is not only associated with in vitro prednisolone resistance, but also correlates (although not significantly) with poor in vivo prednisone responses. Interestingly, the level of S100A8/A9 expression appeared a stronger predictor of a poor clinical outcome than the in vivo prednisone response.…”
Section: Discussionmentioning
confidence: 69%
“…9 However, modulation of MCL1 in prednisolone-resistant MLL-rearranged cell line models only resulted in moderate sensitization, 9,10 implying that other and more relevant resistance mechanisms are involved. In our earlier efforts to define a prednisolone-resistance-associated gene expression profile, the obtained gene signature was compromised by a relatively low accuracy, presumably due to small numbers of patient samples.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, several lines of evidence are in support of Mcl-1 regulation at the translational level. Studies have suggested that, in other contexts, Mcl-1 is a potential downstream target of eIF4E (Wei et al, 2006;Wendel et al, 2007;Mills et al, 2008). Recently Wei et al (2006) described the ability of rapamycin (mTOR inhibitor) to induce Mcl-1 but not Bcl-2 or Bcl-XL block in protein translation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that, in other contexts, Mcl-1 is a potential downstream target of eIF4E (Wei et al, 2006;Wendel et al, 2007;Mills et al, 2008). Recently Wei et al (2006) described the ability of rapamycin (mTOR inhibitor) to induce Mcl-1 but not Bcl-2 or Bcl-XL block in protein translation. Moreover, mir-29b (microRNAs are acting as endogenous sequence that specifically suppress translation) was recently reported to regulate Mcl-1 expression, and its enforced expression made cancer cells sensitive to TRAIL (Mott et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Our group, and others, have demonstrated that rapalogs have an additive or synergistic effect when combined with many agents in vitro, including methotrexate, corticosteroids, doxorubicin, etoposide, and asparaginase. [136,[144][145][146] An added benefit was not found when rapalogs were combined with vincristine in vitro; however, the combination was found to be more effective than either drug alone in vivo. [136,139,146] Rapalogs have been studied in vivo in combination with methotrexate and corticosteroids.…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 99%